The Effect of Nurses' Individual, Professional and Work Environment Characteristics on Their Perception of Quality of Nursing Care - Nilgün Göktepe; Emine Türkmen; İbrahim Fener; Begüm Yalçın; Seda Sarıköse (Association of Nurse Managers, 2021)
Aim: The aim of this study is to examine the effect of nurses' individual, professional and work environment characteristics on their perceptions of quality of care. Method: This cross-sectional study was conducted in a university hospital where 400 nurses were employed, and conducted with 154 nurses who have been working in this hospital for at least one year and volunteered to participate in the study. The data were collected with an online questionnaire consisting of three parts. The survey form contained questions about the personal, professional characteristics, and workplace environment of the nurses, and their satisfaction levels about their perceptions of quality of nursing care, the Practice Environment Scale of the Nursing Work Index. Descriptive statistics and logistic regression analysis were used in data analysis. Results: Nurses rated their perceptions of quality of nursing care (mean score: 7.53+-1.85; range: 0-10). The mean score of nursing work environment scale was 2.77+-0.54. In the logistic regression analysis, it was determined that nurses' perception of quality of nursing care was affected by 'provision of necessary funding sources for quality of nursing care, competency level, staffing and resource adequacy total professional experience, nurse participation in hospital affairs (Nagelkerke R2=58%, p<.05). Conclusion: The nurses' perception of the quality of care is closely related with nursing work environment in the hospital, their perceived self-competence and duration of their professional experience. Support provided by the managers about participation in management processes, providing opportunities for employees to develop their competencies, as well as providing adequate human and other resources in the working environment, will contribute and increase the quality of care.